MUSEUM SONOBUDOYO: PENJAGA WARISAN BUDAYA JAWA DI TANAH MATARAM - Karina Junia M; Intan Nuraeni; Rafka Pramudita P; Kevin Purnama R; Elizabeth Sihombing; Ismi Nur Azzahrah; Deta Sari Mayang W; Ihsan Aenurridha; Hilmi Aditiya F; Aulia Lestari; Dede Wahyu Firdaus (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to analyze the role of the Sonobudoyo Museum as a guardian of Javanese cultural heritage in the Mataram region through a study of its history, collections, and contributions to cultural preservation. The study uses a qualitative descriptive method with a literature study approach that examines journals, institutional documents, and related scientific publications. The results of the study indicate that the Sonobudoyo Museum has a very diverse cultural collection, such as shadow puppets, traditional masks, classical batik, keris and tosan aji, gamelan, and Hindu-Buddhist and Kejawen ritual artifacts, which are not only of historical value but also contain philosophical values ​​and the cultural identity of the Javanese people. In addition to carrying out physical conservation of artifacts, the museum also carries out educational functions through thematic exhibitions, traditional art performances, batik workshops, and gamelan training that play a role in increasing cultural understanding in the younger generation. The Sonobudoyo Museum also plays a role as a research center that provides access to manuscripts, rare artifacts, and cultural data for academics and researchers. These findings conclude that the Sonobudoyo Museum has a strategic role in maintaining the sustainability of Javanese culture through documentation, conservation, education, and art revitalization, so that it is able to maintain local identity amidst the challenges of modernization and globalization.